Особливості впливу статевих стероїдів на органи-мішені та їх взаємозв’язок із моноамінами залежно від клінічного перебігу пубертатних маткових кровотеч - Диннік, В. О.; Суліма, Т. Н. (Clinical Endocrinology and Endocrine Surgery, 2009)
In the investigation of 289 girls with pubertal uterine bleedings it has been shown that clinical course of disease is associated with certain set of the sex steroid hormones: testosterone, estradiol and estriol. It was found that during uterine bleeding sex steroids predetermine catecholamines and serotonin body level. The role of some hormonal patterns in mechanisms and clinical manifestation of three different types of PUB were discussed.